(untitled) (Journal of Science Foundation, 2014)
Background: Infection is an important cause of mortality in burns. Rapidly emerging nosocomial pathogens and the problem of multi-drug resistance necessitates periodic review of isolation patterns and antibiogram in the burn ward. Objective: The purpose of the present study was to see the frequency of bacteria in burn wound with their antibiotic sensitivity pattern. Method: This cross sectional study was conducted in the laboratory of Department of Microbiology at Dhaka Medical College, Dhaka and samples were collected from the burn unit of Dhaka Medical College Hospital, Dhaka. Bacterial isolates from 108 wound swabs taken from burn patients were identified by conventional biochemical methods and antimicrobial susceptibility was performed. Result: Out of 98 bacteria E. coli (20.4%) was most common and 25.0% of these bacteria were ESBL producer. Out of 14 Klebsiella species ESBL producer was in 6(42.9%). ESBL producing Proteus species (21.4%) and Pseudomonas species (14.9%) were also detected. Klebsiella (33.91%) was the predominant organism closely followed by Pseudomonas (31.84%). Conclusion: E. coli is the most common ESBL producing bacteria causing the burn wound infection. DOI: http://dx.doi.org/10.3329/jsf.v10i2.17959 J Sci Found, 2012;10(2):63-69